Morality of Informality: Tax Morale in the Serbian Business Sector – an Empirical Investigation - Radulovic, Branko (Industrija, 2019)
The paper examines the attitudes and perceptions of Serbian businesses regarding justifiability of tax evasion and assess factors that make tax evasion morally acceptable. Using survey of 1,049 businesses in Serbia, the paper finds strong evidence that the negative evaluation of the tax authorities is associated with lower tax morality. Both the ordered logit model (OLM) and the partial proportional odds model (PPOM) as a desirable alternative to OLM were used in the analysis. The perception of the risk of being caught and the overall tolerance of tax evasion are also associated with lower tax morality of businesses (business owners and managers). Results suggest that in the next period it would be important for the Serbian tax authorities to improve how businesses perceive their activities and significantly improve their perception and relationship with business taxpayers.